Proxymate Analysis, Lead and Total Formaldehyde Contents of Squid Eggs Crackers - Denny Syaputra; Eva Prasetiyono (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Trimethylamine N-oxyde (TMAO) known to be breakdown into formaldehyde (H2CO) in the fish-based product such as squid egg crackers or keritcu under high temperature condition of frying. The oral reference dose (RfD) suggested by the US Environmental Protection Agency (EPA) is 0.2 mg formaldehyde per kg body weight per day. Blood lead level should below 5 µg/dL to prevent of reducing cognitive function, decreasing of IQ, and academic achievement. We examine the content of total formaldehyde, leads and proxymate analysis of squid egg crackers. in two different products of halal certificated keritcu in Pangkalpinang. Two different products of halal certificated keritcu were selected after 77 students of junior high school (average body weight was 34 kg), and 95 students of senior high school (avereage body weight was 51,65 kg) in Pangkalpinang city were participated in organoleptic test. High-Performance Liquid Chromatography (HPLC) was conducted to the two products of keritcu in Pangkalpinang city to examine its total formaldehyde. Inductively Coupled Plasma Atomic-Optical Emission Spectrometry (ICP-OES) methods was conducted to examine the leads (Pb) content of two different products of keritcu. SNI 01-2891-1992 methods was conducted for proxymate analysis. In two different products of halal certificated keritcu, no formaldehyde content was detected (limit of detection 1,31 mg/kg), as well as no leads content was detected (limit of detection 0,24 mg/kg). Water content 2,38-2,96%, ash 2,71-3,28%, protein 5,7-6,11%, total lipid 24,39-27,29%, and carbohydrate 61,34-63,84%. Our data show that these two products of keritcu are safe to be consumed by students of junior high school (average body weight was 34 kg) for not more than 5,22 kg keritcu per day, and not more than 7,89 kg keritcu per day for students of senior high school (avereage body weight was 51,65 kg). Leads content of these two products of keritcu (i.e less than 0,24 mg/kg) showed that these products are safe to be consumed.